Aquaponics: integrating fish feeding rates and ion waste production for strawberry hydroponics - Villarroel, M.; Alvariño, J. M. R.; Duran, J. M. (Spanish Journal of Agricultural Research, 2011)
Aquaponics is the science of integrating intensive fish aquaculture with plant production in recirculating water systems. Although ion waste production by f ish cannot satisfy all plant requirements, less is known about the relationship between total feed provided for f ish and the production of milliequivalents (mEq) of different macronutrients for plants, especially for nutrient flow hydroponics used for strawberry production in Spain. That knowledge is essential to consider the amount of macronutrients available in aquaculture systems so that farmers can estimate how much nutrient needs to be supplemented in the waste water from fish, to produce viable plant growth. In the present experiment, tilapia (Oreochromis niloticus L.) were grown in a small-scale recirculating system at two different densities while growth and feed consumption were noted every week for five weeks. At the same time points, water samples were taken to measure pH, EC25, HCO3–, Cl–, NH4+, NO2–, NO3–, H2PO4–, SO42–, Na+, K+, Ca2+ and Mg2+ build up. The total increase in mEq of each ion per kg of feed provided to the fish was highest for NO3-, followed, in decreasing order, by Ca2+, H2PO4–, K+, Mg2+ and SO42–. The total amount of feed required per mEq ranged from 1.61- 13.1 kg for the four most abundant ions (NO3–, Ca2+, H2PO4– and K+) at a density of 2 kg fish m–3, suggesting that it would be rather easy to maintain small populations of fish to reduce the cost of hydroponic solution supplementation for strawberries.